The claimed dravidian influences on southern African societies: some linguistics perspectives (Journal for Studies in Humanities and Social Sciences, 2017)
This paper provides a reaction to and a discussion of the Hromník (1999) paper presented at the Elandsdoorn, Mpumalanga, South Africa symposium, which was also published in a journal. The paper raised thought-provoking associations of some SePedi vocabulary to the Dravidian lan-guages in an attempt to make a connection between the spiritual practices of the two societies. While the reaction and discussion does not question the methodology employed by Hromník (1999), it critically assesses the validity of the associations between the two societies as well as the conclusions that Hromník (1999) arrives at. The paper notes that these conclusions are based on a very limited and nearly insignificant list of vocabulary items which have not been cross-checked, linguistically or historically. This paper further provides some of the procedures that could help to solicit unbiased socio-cultural data that could shed light on possible interactions between SePedi and Dravidian societies, if any. Finally, the paper calls upon linguists, historians and archaeologists to conduct focused research and analyses on this critical issue that Hromník courageously presents.